Export Credit Cover Policies and Payments Difficulties - Puckahtikom, Chanpen (Occasional Papers; Occasional Paper ;, 1985)
In the current environment of payments difficulties, a principal role of the Fund remains the encouragement and support of timely adjustment policies of member countries.